Reductive Cleavage of Certain Azo Dyes by Electrolytically Generated Vanadium (II) in Aqueous Acid Media - Vasanta Kumar Pai, K.; Vasudeva Nayak, P.; Sherigara, B.S. (Asian Journal of Chemistry, 2010)
Vandium(lI) species has been electrolytically generated by the reductionof vanadium(V) sulphate over mercury cathode under nitrogen atmosphereand characterised by literature methods. The reductive estimation of certaincommercially important azo dyes using V(lI) was carried out and theconditions were standardised. The reduction products were identified byTLC-PC methods. The advantages of this method over the Ti(lII) reductionhave been highlighted.